Encapsulation of alpha-mangostin and hydrophilic beta-cyclodextrins revealed by all-atom molecular dynamics simulations - Wiparat Hotarat (2019)
© 2019 The binding affinity of α-mangostin (MGS) inside β-cyclodextrin (βCD) and two of its derivatives, 2,6-dimethyl-β-cyclodextrin (DMβCD) and 2-hydroxypropyl-β-cyclodextrin, hereafter referred to non-specifically as “CDs”, was investigated using molecular dynamics simulations. The reaction pathway starting from free MGS and each CD was simulated, during which several association complexes (the interaction of MGS on exterior CDs cavity) of lower energy than that calculated for the starting geometries could be observed. The inclusion complexes themselves showed even lower binding energies. Moreover, the MM-PBSA calculations revealed that van der Waals forces were the main contribution to the total energy of the complex and that MGS might exist in two energetically similar orientations in the cavity of each CD. Experimental phase solubility assays supported the theoretical investigation and showed that DMβCD is the most efficient for the solubility enhancement of MGS.